A Bibliometric Analysis on Mathematics Learning Interest in Primary Education: A Scopus-Based Review (1982–2025) - Aprina S. P. Hutagalung; Lutfi Nur; Ghullam Hamdu; Aprina S. P. Hutagalung; Lutfi Nur (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Research on mathematics learning interest in primary education has grown rapidly over the past two decades, yet no bibliometric study has systematically mapped its intellectual structure and thematic evolution. This study aimed to map the research landscape of mathematics learning interest in primary education by identifying publication trends, research productivity, and dominant research themes. A bibliometric analysis was conducted on 92 articles indexed in Scopus from 1982 to 2025 using Bibliometrix and VOSviewer. Findings reveal an annual growth rate of 6.66% with a significant surge after 2018, with China, the United States, and Turkey dominating research output. Nine thematic clusters were identified, with dominant themes including mathematics achievement and anxiety, motivation and learning interest, and self-concept and self-efficacy. The fragmented co-authorship network indicates limited international collaboration in this field. These findings provide a comprehensive intellectual map for researchers and education practitioners to identify research gaps and build a more structured collaborative agenda for future inquiry. Research on mathematics learning interest in primary education has grown rapidly over the past two decades, yet no bibliometric study has systematically mapped its intellectual structure and thematic evolution. This study aimed to map the research landscape of mathematics learning interest in primary education by identifying publication trends, research productivity, and dominant research themes. A bibliometric analysis was conducted on 92 articles indexed in Scopus from 1982 to 2025 using Bibliometrix and VOSviewer. Findings reveal an annual growth rate of 6.66% with a significant surge after 2018, with China, the United States, and Turkey dominating research output. Nine thematic clusters were identified, with dominant themes including mathematics achievement and anxiety, motivation and learning interest, and self-concept and self-efficacy. The fragmented co-authorship network indicates limited international collaboration in this field. These findings provide a comprehensive intellectual map for researchers and education practitioners to identify research gaps and build a more structured collaborative agenda for future inquiry.